Motivation and job satisfaction of community health workers in Ethiopia: a mixed-methods approach - Yohannes Ejigu; Netsanet Abera; Werissaw Haileselassie; Negalign Berhanu; Biniyam Tadesse Haile; Frehiwot Nigatu; Nurhan Tewfik; Yibeltal Kiflie; Girmay Medhin; Fasil Walelign; Mekdes Demissie; Setegn Tigabu; et al. (BMC, 2023)
Abstract Background Ethiopia has been providing health care to its rural population since 2004 using female Community Health Workers called Health Extension Workers (HEWs). The HEWs are credited with several achievements in improving the country's health indicators. However, information about the HEWs' motivation and job satisfaction is limited. The aim of this study was to assess the HEWs' motivation and job satisfaction, as well as the factors that influence them. Methods A mixed-methods study was nested within a national health extension program assessment conducted from March 01 to May 31, 2019. A structured questionnaire which looked at motivation and satisfaction with Likert type single-question and multiple-item measures was used to collect quantitative data from 584 HEWs. Focus group discussion and in-depth interviews were used to gather qualitative data. Means and percentages were used to descriptively summarize important variables. Linear regression was used to identify factors associated with job satisfaction. The qualitative data was analysed thematically. Results Overall, 48.6% of HEWs were satisfied with their job, with a mean score of 2.5 out of 4.0. The result showed a high level of satisfaction with autonomy (72%), relationships with co-workers (67%), and recognition (56%). Low level of satisfaction was linked to pay and benefits (13%), opportunities for promotion (29%), and education (34%). Regression analysis showed that HEWs in the age category of 30 years and older had lower satisfaction scores as compared to HEWs in the age category of 18-24 years (adjusted β = − 7.71, 95% CI: − 14.42, − 0.99). The qualitative result revealed that desire to help their community, recognition or respect gained from the community, and achievement were the major motivating factors. In contrast, inadequate pay and benefit, limited education and career advancement opportunities, workload, work environment, limited supportive supervision, and absence of opportunity to change workplace were the demotivating factors. Conclusions The overall job satisfaction of HEWs was low; extrinsic factors, such as inadequate pay, limited education and career advancement opportunities were the major sources of demotivation. Policy makers and human resource managers should revise their human resource policies and guidelines to address the main sources of low level of job satisfaction and demotivation.